Penerapan Model Pembelajaran Cooperative Tipe Student Team Achievement Divisions (STAD) Untuk Meningkatkan Prestasi Belajar Siswa Kelas IV SD Dwijendra - Yohana Unyat Semantik (PEDIR: Journal of Elementary Education, 2021)
This study aims to improve the student’s achievement through the application of the STAD cooperative learning model. This is a classroom action research (CAR) which is according to Sanjaya; this research was conducted in two cycles, which included four stages: planning, implementing, observing and reflecting. The sample of this research is the fourth grade students of SD Dwijendra which consist of 35 students; 15 male and 20 female. The data of student learning achievement were collected by means of learning achievement tests which then analyzed by descriptive quantitative analysis. The research results shows an improvement in the percentage of student learning achievement by 11.14% from 69.14% in cycle 1 with moderate criteria to 80.28% in cycle II with high criteria. Pre-cycle classical completeness of 28.57% increased by 45.71% to 74.28% in cycle I increased again by 11.29% to 85.57% in cycle II. Based on these results, it can be concluded that the implementation of the STAD cooperative learning model can improve the learning achievement of the fourth grade students of SD Dwijendra Denpasar.